2019
DOI: 10.1002/eap.2004
|View full text |Cite
|
Sign up to set email alerts
|

Slow rate of secondary forest carbon accumulation in the Guianas compared with the rest of the Neotropics

Abstract: Secondary forests are a prominent component of tropical landscapes, and they constitute a major atmospheric carbon sink. Rates of carbon accumulation are usually inferred from chronosequence studies, but direct estimates of carbon accumulation based on long‐term monitoring of stands are rarely reported. Recent compilations on secondary forest carbon accumulation in the Neotropics are heavily biased geographically as they do not include estimates from the Guiana Shield. We analysed the temporal trajectory of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 66 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…Thus, the accumulation of AGB with age follows different trends across sites, as already highlighted in previous studies (Kennard et al, 2002;Poorter et al, 2016a;Ray and Brown, 2006;Ruiz et al, 2005;Silver et al, 2000;Toledo and Salick, 2006). Understanding how these trends vary according to abiotic factors (e.g., soil type, rainfall), species assemblage and diversity, and prioritizing effects such as types of land use and land management existing before forest recolonization, constitute an important avenue of research (Chazdon, 2014;McMahon et al, 2019).…”
Section: Agb Recovery Through Timementioning
confidence: 79%
See 1 more Smart Citation
“…Thus, the accumulation of AGB with age follows different trends across sites, as already highlighted in previous studies (Kennard et al, 2002;Poorter et al, 2016a;Ray and Brown, 2006;Ruiz et al, 2005;Silver et al, 2000;Toledo and Salick, 2006). Understanding how these trends vary according to abiotic factors (e.g., soil type, rainfall), species assemblage and diversity, and prioritizing effects such as types of land use and land management existing before forest recolonization, constitute an important avenue of research (Chazdon, 2014;McMahon et al, 2019).…”
Section: Agb Recovery Through Timementioning
confidence: 79%
“…Tropical forest disturbances and subsequent biomass recovery through time significantly affect the global carbon cycle (Harris et al, 2012). Although secondary forests in the tropics could constitute a major global carbon sink, the magnitude of such a sink remains poorly known (Chazdon, 2014;Lugo and Brown, 1992). A previous study estimated that 40 years of carbon storage in regenerating tropical forests from Latin America offset the past 19 years of carbon emissions from fossil fuels and industrial production in this region (Chazdon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the plots (~60%) also began growing before 1985 (Requena Suarez et al., 2019), when large‐scale deforestation had not yet substantially reduced forest cover (Fearnside, 2005) and before mechanized agriculture had intensified land use. Recent studies from other regions have shown much lower carbon accumulation rates of 2.25 Mg ha −1 year −1 in Paragominas and Santarém‐Belterra (Lennox et al., 2018), 1.08 Mg ha −1 year −1 in Bragança (Elias et al., 2019) or as low as 0.89 Mg ha −1 year −1 in the Guiana Shield (Chave et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While the carbon balance of undisturbed forests has been well studied (Brienen et al, 2015;Hubau et al, 2020;Pan et al, 2011;Saatchi et al, 2011), estimates of the rate of carbon sequestration in secondary forests remain highly variable (Elias et al, 2019;Grace et al, 2014;Pan et al, 2011;Saatchi et al, 2011 (Elias et al, 2019) or as low as 0.89 Mg ha −1 year −1 in the Guiana Shield (Chave et al, 2020).…”
Section: Uncertainty In the Role Of Secondary Forests As A Carbon Sinkmentioning
confidence: 99%
“…The sheer size of the Amazon, its environmental heterogeneity, and species diversity pose challenges and practical difficulties to understand general ecological relationships and biogeographical patterns (Tuomisto et al, 2019). Forest inventory plots provide many valuable insights to investigate the influences of the environment on tree height but they only represent a minuscule fraction of the total forest area (Chave et al, 2020). Currently, a network of 5,351 forest inventory plots established across the Brazilian Amazon, of known and published sites recently compiled by Tejada et al (2019), represents only 0.0013% of the total forest area in this region.…”
Section: Introductionmentioning
confidence: 99%